Investigating Critical Thinking Indicators in the Context of Algebra Problem Solving: A Study in Indonesia - Qurohman, M. Taufik; Wijayanto , Zainnur; Suwarto , Suwarto (Utamax : Journal of Ultimate Research and Trends in Education, 2025)
Developing students’ critical thinking in mathematics, particularly in algebra problem solving, is crucial for enhancing conceptual understanding and mathematical reasoning. Although critical thinking has been widely studied, limited research has specifically examined how Indonesian students demonstrate critical thinking in algebra tasks, especially in the evaluation stage. This study investigates how students engage with four key indicators of critical thinking: Analysis, Strategy, Inference, and Evaluation, during algebra problem solving. A qualitative descriptive approach was employed, involving six purposively selected eleventh-grade students from Senior High School 5 Tegal, categorized into high, medium, and low levels of critical thinking ability. Data were gathered through classroom tests, structured observations, and in-depth interviews, then analyzed using thematic coding with triangulation to ensure credibility. The results indicate that students with high critical thinking levels were able to perform all four indicators effectively, while those at the medium level showed inconsistent performance, particularly in the inference and evaluation stages. Students with low critical thinking levels struggled to identify mathematical structures, often applying procedures without conceptual clarity. These findings suggest that the quality of students’ critical thinking is closely related to their algebraic understanding and ability to apply reasoning strategies. This study highlights the underexplored evaluation dimension of critical thinking, offering new insights into how students validate and justify solutions in mathematics. The findings underscore the need for instructional practices that support reflective thinking, encourage reasoning, and promote deeper engagement with mathematical problems. Further research is recommended to explore how these skills develop across time and educational contexts.